Filipino-ness and the heterosexual matrix in the work of Gregorio Brillantes - Ade, Wernmei Y. (Asian Perspectives in the Arts and Humanities, 2013)
This paper is an attempt to substantiate J. Neil M. Garcia’s endorsement of Butlerian performativity in assessing what constitutes Filipino-ness, and how that Filipino-ness is constituted in post-Independence Filipino literature, focusing on two short stories by Gregorio Brillantes. Caroline Hau argues that literature is one of the structures of intelligibility through which we imagine ourselves as a nation, and ourselves as belonging to a particular nation. The Rizal Bill, passed in 1956, attested to “the exis- tence of a disciplinary space, an ensemble of discourses and practices constituting the field of literary education over which the Philippine state sought continually to extend the scope of its nation-building projects” (Hau 1). Literature was enlisted as a means to regulate the performance of Filipino-ness; literature, as Hau’s performative lexicon suggests, also performed Filipino-ness. If literature as a disciplinary practice indeed has the ability to intervene in national history, then it becomes necessary to ask, “How does literature ‘represent’ (in both artistic and political senses of the word) the ‘true’ Filipino national community? How does literature address, and resolve, the problem posed by the foreign, especially colo-nial ‘influences’ on Philippine national culture? How does literature imag-ine the ‘foreigner’ within the Filipino nation? How does literature forge the link between the personal and the political?” (Hau 9). Given its central place as a disciplinary practice in nation-imagining, what literature does has definite bearing on what Filipino-ness is. This paper answers the questions Hau raises in the context of Brillantes’ short stories.